2008
DOI: 10.1007/s11517-008-0423-y
|View full text |Cite
|
Sign up to set email alerts
|

The use of microbubbles in Doppler ultrasound studies

Abstract: Ultrasound contrast agents (UCAs) are widely used in Doppler studies, either for simple echo enhancement purposes, or to increase the low signal-to-clutter ratio typical of microcirculation investigations. Common to all Doppler techniques, which are briefly reviewed in this paper, is the basic assumption that possible phase and amplitude changes in received echoes are only associated with UCA microbubble movements due to the drag force of blood. Actually, when UCAs are insonified, phenomena such as rupture, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…The peak velocities obtained were 12.5, 46 and 68 cm/s; these are slightly higher than the analytical peak velocities derived from the measured flow rates obtained using a bucket and stopwatch, which were 10, 38 and 59 cm/s. The discrepancy is probably due to an imperfect setting of spectral Doppler angle and the broadening of the Doppler spectrum by microbubbles (Tortoli et al 2009). …”
Section: Straight-vessel Phantommentioning
confidence: 99%
“…The peak velocities obtained were 12.5, 46 and 68 cm/s; these are slightly higher than the analytical peak velocities derived from the measured flow rates obtained using a bucket and stopwatch, which were 10, 38 and 59 cm/s. The discrepancy is probably due to an imperfect setting of spectral Doppler angle and the broadening of the Doppler spectrum by microbubbles (Tortoli et al 2009). …”
Section: Straight-vessel Phantommentioning
confidence: 99%
“…Another distinct observation from previous studies is that their observed Doppler effect appeared as a broadening of the harmonic peak (Tortoli et al 2000, 2005) while we observed a distinct peak that can be quantified and characterized. The reasons are that previous studies examined the fundamental frequency and that the shifts were not due to continuous translation of the acoustic sources, but due to the inter-pulse microbubble movement during the off-time of the sequence (Tortoli et al 2009). Hence, whereas the instantaneous m s −1 velocities should translate into tens of kHz of frequency shift, the detected broadening was constrained to a few hundreds of Hz (Tortoli et al 2005, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The reasons are that previous studies examined the fundamental frequency and that the shifts were not due to continuous translation of the acoustic sources, but due to the inter-pulse microbubble movement during the off-time of the sequence (Tortoli et al 2009). Hence, whereas the instantaneous m s −1 velocities should translate into tens of kHz of frequency shift, the detected broadening was constrained to a few hundreds of Hz (Tortoli et al 2005, 2009). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed in the paper by Tortoli et al [8] they are widely used in Doppler studies, especially in the microcirculation, to improve the signal-to-noise ratio. Interpretation of the microbubble signals can however be complicated not only by their non-linearity, but also by a variety of phenomena including destruction, deflation and displacement of microbubbles due to radiation force.…”
mentioning
confidence: 99%